Violation of human rights in Tunja education - Gómez-Barreto, Manuel Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Colombian education assumes quality and gratuity policies aimed at protecting human rights in pedagogical framework. This paper addresses an analysis of the development of these policies in the city of Tunja, to give an overview about the violation of human rights in teaching, assuming the various agreementsmade for their protection, without separating the different processes that quality education requires. It was taken into account international policies of educational protection and quality, and the analysis is based on actual statistics issued by the local authorities.